PANDEMIC EFFECT TOWARDS RESIDENTIAL PROPERTIES IN BANDUNG AREA - Ivanka Yelizaveta Lazuardi; Raden Aswin Rahadi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
COVID-19 has affected almost all business sectors in Indonesia, including real estate. This research is purposed to examine the condition of residential properties around the Bandung area after the COVID-19 pandemic. The objectives of the research are to recognize some factors affecting the performance of housing properties and to give recommendations for the future strategy of residential properties in the city. By reviewing some reviewed papers and preliminary studies, the author concluded the current residential property industry is mostly having a setback such as; low development, drop housing prices, low demand, layoffs, and evictions. The research will use a semi-structured interview to analyse the real condition in Bandung city, and the author targeted four main stakeholders to be interviewed which are; real estate agents, property developers, consumers, and government officials. Furthermore, this research would be beneficial to all the stakeholders to handle the pandemic situation that might happen in the future and prepare the best strategy for this industry so the business could run well.